UJI VALIDITAS DAN RELIABILITAS INSTRUMEN KOMPETENSI KERJA MAHASISWA - Putri Anditasari; Yusi Riksa Y (Jurnal Evaluasi Pendidikan, 2026)
This study examines the validity and reliability of a student work competency instrument designed to measure underlying individual characteristics causally related to effective and superior performance. The instrument is developed based on the Spencer and Spencer competency model, which includes five dimensions: motive, trait, self-concept, knowledge, and skill. Measurement uses behavioral indicators distinguishing superior and threshold performance as indicators of students’ readiness to meet workplace demands. This study employed a descriptive quantitative approach involving 209 undergraduate students from higher education institutions as participants in an instrument try-out. Item validity was assessed using corrected item–total correlation, while reliability was examined using Cronbach’s Alpha. Results indicated that 48 of 60 tested items were valid. Reliability analysis produced a Cronbach’s Alpha coefficient of 0.945, indicating very high internal consistency. Overall, the findings demonstrate that the instrument is reliable and suitable for assessing student work competencies and supporting students’ readiness for career transition.